2021
DOI: 10.1007/s12678-021-00647-w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Oxidation Reaction on a 4-Mercaptopyridine Self-Assembled Monolayer on Au(111) Metallized by Platinum Nanoislands

Abstract: A systematic investigation of the hydrogen peroxide oxidation reaction (HPOR) in phosphate buffer (pH = 7.3) on an Au(111) single crystal modified with a 4-mercaptopyridine self-assembled monolayer (SAM) has been conducted before and after metallization with Pt. While bare Au(111) shows considerable electrocatalytic activity towards the HPOR, the inhibition of the oxidation reaction after modification with the SAM implies that adsorbed 4-mercaptopyridine molecules do not catalyze the HPOR. However, SAM-modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Other electrocatalysts for HPOR include nickel/nickel oxide embedded N-graphene [97] cobalt phthalocyanine, [98] hollow cobalt nitrogen doped carbon catalyst, [99] and platinum nano islands on Au (111). [100] It was shown that vitamin B12 can be used as an electrocatalyst for HPOR at physiological pH values. [101] For the anode, as well as for the cathode, it is important to have a special 3D morphology.…”
Section: Materials Requirements For H 2 O 2 Fcmentioning
confidence: 99%
“…Other electrocatalysts for HPOR include nickel/nickel oxide embedded N-graphene [97] cobalt phthalocyanine, [98] hollow cobalt nitrogen doped carbon catalyst, [99] and platinum nano islands on Au (111). [100] It was shown that vitamin B12 can be used as an electrocatalyst for HPOR at physiological pH values. [101] For the anode, as well as for the cathode, it is important to have a special 3D morphology.…”
Section: Materials Requirements For H 2 O 2 Fcmentioning
confidence: 99%
“…Compared to the well-established approach using chemically inert SAMs, [1][2][3][4][5][6][7] functionalised layers bearing metal coordinating moieties change the paradigm from defect-based electrodeposition to deposition controlled by molecular properties. The different mechanism not only confines deposition to on top of the SAM as first reported by Kolb et al [8][9][10] but the level of control over the deposition process offers new prospects for the design of materials as illustrated by the tuning of electronic properties, [11][12][13][14][15][16] generation of SAM/metal hybrid structures, 17 control of catalytic activity, 12,18,19 the epitaxial growth of Cu films on a cysteine modified Au surface, 20 or the generation of bimetallic nanostructures. 21 Coordination-controlled electrodeposition (CCED) can be accomplished in different ways and the ones employed in the work presented here are illustrated in Fig.…”
mentioning
confidence: 99%